Pengembangan Keterampilan Santri dalam Pembuatan Produk Makanan - Atik Dwi Kristanti; Rahman Amrullah Suwaidi (Journal on Education, 2025)
Al-Itqon Tahfidzul Qur’an Islamic Boarding School, located in Jombang, East Java, has taken on an important role not only as a center for religious education but also as a driver of local economic development. The boarding school has attempted to integrate educational values ​​with economic initiatives, particularly through the processing and marketing of tuna floss, a local product with great potential but not yet fully marketed. The main obstacles faced include lack of knowledge in product and production, limited market access, and insufficient production capacity. In order to overcome these challenges, this community service activity focused on developing innovative branding strategies and increasing business management capacity for students and the local community. This service program implemented a series of interactive and inclusive methods, including SWOT analysis, intensive training, and socialization sessions designed to facilitate community involvement. The main goal was to not only increase the appeal of the product but also integrate Islamic values ​​into sustainable business practices. The results of this program showed significant increases in production capacity and market access, which positively impacted the income of local producers and created new job opportunities. The implementation of effective digital marketing techniques strengthens the economic independence of Islamic boarding schools and communities, and supports sustainable economic development in other Islamic boarding schools in Indonesia. The Tahfidzul Qur'an Al-Itqon Islamic Boarding School demonstrates the role of Religious Education Institutions in inclusive socio-economic growth.